Tagging SNPs within regulatory parts of APOA5 and CYP7A1 genes and their expression in human liver tissue: a pilot study. (1st December 2016) - Dlouha, Dana; Oliverius, Martin; Hubacek, Jaroslav Alois; Lesna, Ivana Kralova; Lanska, Vera; Poledne, Rudolf
Abstract: Objective: Apolipoprotein A5 (lipoprotein lipase activator) and cholesterol 7 α -hydroxylase (microsomal cytochrome P450) are almost exclusively expressed in liver tissue. Variants within the regulatory parts of these genes (rs662799 and rs3135506 within APOA5 and rs3808607 within CYP7A1 ) can probably affect levels of plasma lipids and may influence the success of the treatment of dyslipidaemia.Methods: In order to conduct a primary analysis of whether the effect of the variants is mediated through gene expression, we collected and analysed 25 anonymous samples of human liver tissue.Results: APOA5 expression levels of hepatic mRNA were lower in carriers of at least one less common APOA5 allele than in common alleles homozygotes, but the difference was not significant ( p  = 0.19), mainly due to the huge expression range in different samples. Similarly, CYP7A1 expression was also not significantly influenced by the promoter variant, regardless of the type of statistical model used (all p  > 0.31). In our study, we have detected a huge inter-individual variation in the hepatic transcript levels of APOA5 and CYP7A1 . These inter-individual variations were the main reasons why having even twice as high levels of expression between the compared groups with different genotypes was not significant.Conclusions: The results of our pilot study did not confirm a possible effect of promoter variants on the expression of APOA5 and CYP7A1 genes. The relatively small sample size could have affected our results. A central facility based on international collaboration that collects liver resection material may help increase the number of samples to provide meaningful results.